The use of femtosecond lasers in cataract surgery: review of the published results with the LenSx system - Nagy, Zoltán Zsolt; Mastropasqua, Leonardo; Knorz, Michael C. (Journal of refractive surgery, 2014)
PURPOSE: To review the published literature describing the use of the LenSx femtosecond laser technology (Alcon Laboratories, Inc., Fort Worth, TX) in cataract surgery. - METHODS: Literature review. - RESULTS: The LenSx system has been used in more than 200,000 cataract surgery procedures to date. Pre-clinical evaluations have shown that this system produces accurate and reproducible capsulorhexes, and that both the energy required for phacoemulsification and total phacoemulsification time are less than with conventional phacoemulsification. In comparative studies, femtosecond lasers have been shown to produce more precise and reproducible capsulorhexes than manual procedures, and better intraocular lens placement; capsule overlap, circularity of capsulotomy, and centration of the intraocular lens are consistently better with femtosecond lasers than with manual procedures. The improved quality of capsulorhexis and intraocular lens positioning are reflected in favorable visual and refractive outcomes. As with any new technology, there is a significant learning curve: prospective cohort studies have shown that the incidence of intraoperative complications such as suction breaks or anterior capsular tears or tags decreases with experience. In general, the incidence of such complications is within the range (< 2%) considered in recent evidence-based guidelines to be feasible and desirable. - CONCLUSIONS: Although femtosecond laser cataract surgery is in its infancy, the technology is evolving rapidly and offers the potential for more consistent and predictable results after cataract surgery.